2022
DOI: 10.1007/jhep05(2022)062
|View full text |Cite
|
Sign up to set email alerts
|

Diquark properties from full QCD lattice simulations

Abstract: We study diquarks on the lattice in the background of a static quark, in a gauge-invariant formalism with quark masses down to almost physical mπ. We determine mass differences between diquark channels as well as diquark-quark mass differences. The lightest and next-to-lightest diquarks have “good” scalar, $$ {\overline{3}}_F $$ 3 ¯ F , $$ {\overline{3}… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Further details and supporting studies that go beyond the scope of this contribution can found in Ref. [16]. The results shown here were taken from this main reference.…”
Section: Discussion and Summarymentioning
confidence: 88%
See 1 more Smart Citation
“…Further details and supporting studies that go beyond the scope of this contribution can found in Ref. [16]. The results shown here were taken from this main reference.…”
Section: Discussion and Summarymentioning
confidence: 88%
“…not gauge-invariant, and the lattice cannot access them directly. In this contribution, based on the work of [16], we address this issue by forming gauge-invariant probes of diquark properties through embedding them in hadrons that contain in addition a single static quark. The mass of this infinitely heavy quark cancels exactly in mass differences.…”
mentioning
confidence: 99%
“…Further details and supporting studies that go beyond the scope of this contribution can found in [19]. The results shown here were taken from this main reference.…”
Section: Discussion and Summarymentioning
confidence: 92%
“…We also compare with new quenched simulations with a valence pion mass 𝑚 𝑣 𝜋 = 909 MeV. All reported results are based on [19].…”
Section: Pos(ichep2022)795mentioning
confidence: 99%